Vietnam : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Vietnam during 1992-96. Economic growth was recorded at 8-9 percent during 1992-94, rising to a 9 1\2 percent annual rate in 1995 and the first half of 1996. Investment has been rising steadily over the past few years, owing in part to foreign investment, which increased to 9 percent of GDP in 1995 and continued to rise strongly in 1996. Vietnam's foreign trade has also expanded and diversified rapidly, with both imports and exports growing at double-digit annual rates.